2021
DOI: 10.1155/2021/2790958
|View full text |Cite
|
Sign up to set email alerts
|

The Auxiliary Diagnosis and Imaging Characteristics of MRI Combined with CT in Patients with Cholangiocarcinoma

Abstract: Background. Patients with cholangiocarcinoma (CCA) have poor prognosis and high mortality. Therefore, early detection and early diagnosis are extremely important to control the development of CCA. This study aims to explore the diagnostic effect in patients with CCA and imaging characteristics of MRI combined with CT. Methods. 109 patients with suspected CCA underwent CT and MRI before diagnosis. The examination results were compared with the “gold standard.” ROC curve was drawn to analyze the diagnostic effic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…On MRI, ICC typically appears hypointense on T1-weighted imaging and hyperintense on T2-weighted imaging, with contrast enhancement patterns like those found on CT [10]. Both CT and MRI are the imaging modalities of choice for diagnosing cholangiocarcinoma, but both combined have a higher sensitivity and specificity than each of them alone [11]. It is believed that the more sclerosing tumors intend to invade the ductal wall earlier, thus leading to lower cure rates.…”
Section: Discussionmentioning
confidence: 99%
“…On MRI, ICC typically appears hypointense on T1-weighted imaging and hyperintense on T2-weighted imaging, with contrast enhancement patterns like those found on CT [10]. Both CT and MRI are the imaging modalities of choice for diagnosing cholangiocarcinoma, but both combined have a higher sensitivity and specificity than each of them alone [11]. It is believed that the more sclerosing tumors intend to invade the ductal wall earlier, thus leading to lower cure rates.…”
Section: Discussionmentioning
confidence: 99%
“…MRI is of high value in preoperative staging, resectable evaluation, selection of surgical methods, and evaluation of prognosis of cholangiocarcinoma. Li reported that the combination of enhanced CT and MRI in the diagnosis of cholangiocarcinoma has high sensitivity and specificity, which can provide an imaging basis for clinical diagnosis and treatment ( 12 ). In addition, studies have reported the dense accumulation of the nucleotide tracer 18-fluorodeoxyglucose ( 18 F-FDG) in cholangiocarcinoma ( 13 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although it is an important imaging technique commonly used to examine abdominal disease, CT also shows relatively low accuracy in detecting biliary disorders. According to recent studies, we estimated that the specificity was 67.1–88.2%, sensitivity was 79.4–90.4%, and accuracy was 74.6–89.3% in the differentiation of benign and malignant bile duct strictures [7,8]. MRCP is a valuable tool in the investigation of biliary duct dilatation with relatively high sensitivity and specificity [9,10].…”
Section: Introductionmentioning
confidence: 99%